2022
DOI: 10.3390/ph16010047
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mast Cell Stabilizer JM25-1 Rehabilitates Impaired Gut Barrier by Targeting the Corticotropin-Releasing Hormone Receptors

Abstract: Mast cell (MC) plays a central role in intestinal permeability; however, few MC-targeting drugs are currently available for protection of the intestinal barrier in clinical practice. A nonfluorinated Lidocaine analog 2-diethylamino-N-2,5-dimethylphenyl acetamide (JM25-1) displays anti-allergic effect, but its impact on MC remains elusive. In this study, we explored whether JM25-1 has therapeutic potential on intestinal barrier defect through stabilizing MC. JM25-1 alleviated release of β-hexosaminidase and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…Although we did not examine the intestinal permeability after CRFR antagonist, a recent study showed that impaired gut barrier was recovered by targeting the CRFRs on mast cells. 52 Although we did not determine whether the relationship between increased ileal permeability and changes in CRFR in the rectum are independent or interacting, further exploration of these relationships may lead to a better understanding of the pathophysiology of this model.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although we did not examine the intestinal permeability after CRFR antagonist, a recent study showed that impaired gut barrier was recovered by targeting the CRFRs on mast cells. 52 Although we did not determine whether the relationship between increased ileal permeability and changes in CRFR in the rectum are independent or interacting, further exploration of these relationships may lead to a better understanding of the pathophysiology of this model.…”
Section: Discussionmentioning
confidence: 89%
“…Those mediators impair the tight junction between the intestinal epithelial cells, whose release from mast cells might be suppressed by CRFR antagonism, leading to rapid suppression of visceral hypersensitivity as shown in our study. Although we did not examine the intestinal permeability after CRFR antagonist, a recent study showed that impaired gut barrier was recovered by targeting the CRFRs on mast cells 52 . Although we did not determine whether the relationship between increased ileal permeability and changes in CRFR in the rectum are independent or interacting, further exploration of these relationships may lead to a better understanding of the pathophysiology of this model.…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between manifestations of stress and reactions from the gastrointestinal tract is mediated by the interaction of the brain and mast cells with the participation of the vagus nerve [56,57]. The further process of mast cell degranulation increases the permeability of the intestinal barrier, and pharmacological inhibition of their activation eliminates this effect in animal stress models [58][59][60]. Intestinal microorganisms (bacteria, fungi, etc.)…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%
“…Взаємозв'язок між проявами стресу та реакціями з боку шлунково-кишкового тракту опосередковується взаємодією мозку і мастоцитів за участі блукаючого нерва [56,57]. Подальший процес дегрануляції мастоцитів посилює проникність кишкового бар'єру, а фармакологічне інгібування їх активації нівелює цей ефект на моделях стресу у тварин [58][59][60]. Кишкові мікроорганізми (бактерії, грибки тощо) можуть індукувати активацію тучних клітин [5,61], причому деякі мікроорганізми можуть викликати прозапальну реакцію, в той час як інші можуть її зменшити, що дозволяє модулювати інтенсивність та перебіг запалення і таким чином сприяти підтримці гомеостатичних умов у слизовій оболонці кишок [4,62].…”
Section: огляди літератури / Literature Reviewsunclassified